1993
DOI: 10.1111/j.1365-2672.1993.tb02758.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydroxycinnamic acids on the growth of wine‐spoilage lactic acid bacteria

Abstract: Hydroxycinnamic acids and their derivatives occur naturally in grape juice and wine. To assess their potential as natural preservatives the effect of caffeic, coumaric and ferulic acids on the growth of three wine‐spoilage strains of Lactobacillus collinoides and one of Lact. brevis was studied in acid tomato broth containing 5% ethanol at pH 4.8. At concentrations of 500 and 1000 mg l‐1, all three compounds markedly inhibited growth; coumaric and ferulic acids were more effective than caffeic acid. At a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…In a recent study where the effect of oregano and cinnamon essential oils at 400 mg/kg level on fermentation quality and aerobic stability of field pea silage were investigated it was reported that both additives reduced dry matter losses and prevented the cell wall materials of silages [19] . In the present study, DTP addition increased the ADF and NDF levels of both [20] . These finding were in agreement with the results of Soycan Önenç et al [19] .…”
Section: Discussionsupporting
confidence: 66%
“…In a recent study where the effect of oregano and cinnamon essential oils at 400 mg/kg level on fermentation quality and aerobic stability of field pea silage were investigated it was reported that both additives reduced dry matter losses and prevented the cell wall materials of silages [19] . In the present study, DTP addition increased the ADF and NDF levels of both [20] . These finding were in agreement with the results of Soycan Önenç et al [19] .…”
Section: Discussionsupporting
confidence: 66%
“…Comparable results have been reported in previous investigations. Stead [25] found that high concentrations of p-coumaric, ferulic and caffeic acids inhibited the growth of Lactobacillus collinoides and Lactobacillus brevis, whereas low concentrations stimulated their growth. In another study, Rozès and Peres [26] observed that caffeic and ferulic acids negatively affected the growth of L. plantarum and increased the proportion of unsaturated fatty acids of the cell membrane.…”
Section: Influence Of Phenolic Compounds On the Growth Of Lactic Acidmentioning
confidence: 99%
“…Spontaneous MLF commonly occurs after alcoholic fermentation when wine conditions are favourable for the growth of lactic acid bacteria, however spontaneous MLF is unpredictable, hence the importance of using commercial starters. Regarding low molecular weight phenolic compounds it is known that some phenolic acids can inhibit the growth of lactic acid bacteria [9] while others can stimulate malolactic fermentation carried out by Oenococus oeni [10][11][12]. During this process hydroxycinnamic acids and their derivatives are the main compounds modified.…”
Section: E-mail Address: Afreitas@uevorapt (Am Costa Freitas)mentioning
confidence: 99%